Identification and Functional Analysis of Three Isoforms of Bovine BST-2 - Takeda, Eri (Public Library of Science, 2012)
Human BST-2 (hBST-2) has been identified as a cellular antiviral factor that blocks the release of various enveloped viruses. Orthologues of BST-2 have been identified in several species, including human, monkeys, pig, mouse, cat and sheep. All have been reported to possess antiviral activity. Duplication of the BST-2 gene has been observed in sheep and the paralogues are referred to as ovine BST-2A and BST2-B, although only a single gene corresponding to BST-2 has been identified in most species. In this study, we identified three isoforms of bovine BST-2, named bBST-2A1, bBST-2A2 and bBST-2B, in bovine cells treated with type I interferon, but not in untreated cells. Both bBST-2A1 and bBST-2A2 are posttranslationally modified by N-linked glycosylation and a GPI-anchor as well as hBST-2, while bBST-2B has neither of these modifications. Exogenous expression of bBST-2A1 or bBST-2A2 markedly reduced the production of bovine leukemia virus and vesicular stomatitis virus from cells, while the antiviral activity of bBST-2B was much weaker than those of bBST-2A1 and bBST-2A2. Our data suggest that bBST-2A1 and bBST-2A2 function as part of IFN-induced innate immunity against virus infection. On the other hand, bBST-2B may have a different physiological function from bBST-2A1 and bBST-2A2.